Literasi Keuangan, Persepsi Risiko Keuangan, dan Perilaku Keuangan Terhadap Keputusan Investasi Cicil Emas - Ni'mah, Fika Ulin; Indriasari , Ika; Nastiti, Prianka Ratri (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the influence of Financial Literacy, Financial Risk Perception, and Financial Behavior on Gold Installment Investment Decisions. The approach used is quantitative with primary data sources collected through questionnaires. The population used in this study consists of customers of PT Bank Syariah Indonesia KC Pati Sudirman who have made gold installment investments. This study employs Non-Probability Sampling with a sample size of 160 respondents. Measurements in this study used a Likert scale, wich was then processed using IBM SPSS Statistics Version 25 with multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between financial literacy and investment decisions, financial risk perception has a positive and significant influence on investment decisions, and financial behavior has a positive and significant influence on investment decisions. The results of the coefficient of determination (R2) test yielded an Adjusted R2 value of 0,461 or 46,1%, indicating that the investment decisions variable is influenced by financial literacy, financial risk perception, and financial behavior, while the remainder is influenced by variables outside the scope of this study.